A Study on the Use of Necuron-Type Polymer Plastics utilized for Sliding Bearing Manufacturing - Nae, Ion; Zisopol, Dragos Gabriel; Romanet, Mirela; Bogdan-Roth, Mihai; Ramadan, Ibrahim (Engineering, Technology & Applied Science Research, 2025)
This paper presents research on the characteristics of the thermoplastic materials used in the manufacture of sliding bearings. Two types of materials from the category of thermosetting polyurethanes with the commercial names Necuron 1050 and Necuron 1300 were investigated. Tests were conducted to determine their physical and mechanical characteristics, such as density, hardness, tensile strength, compressive strength, and longitudinal modulus of elasticity. The results obtained during the study attest to the quality of the materials in the thermosetting polyurethane category in terms of hardness, tear resistance, and compression resistance. The materials in the category of thermosetting polyurethanes stand out as the right choice for applications that require mechanical strength, durability, and resistance to environmental factors.